The Relationship Between Knowledge And Attitudes Of Prospective Couples (Catin) Regarding Pregnancy Preparation At KUA Galis, Bangkalan Regency (International Journal of Education and Literature, 2024)
Pregnancy is an important period of life, during that time you must prepare yourself as best as possible to welcome the birth of your baby. Factors that influence maternal health are nutrition. Chronic energy deficiency (KEK) can disrupt health and has the risk of having an adverse impact on the mother and baby both during pregnancy, childbirth and postpartum, such as inhibiting fetal growth which can lead to abortion, birth of low birth weight (LBW) babies, anemia in babies and death. neonate . Catin knowledge is very influential in actions to prepare for a healthy pregnancy. The research aims to determine the relationship between knowledge and attitudes of catin couples regarding pregnancy preparation at KUA Galis . This research design uses correlational analytics with a cross sectional approach , namely research that leads to explaining data on the independent variable (knowledge) and the dependent variable (attitudes of catin). The results of this research show that most of the knowledge possessed by catin couples is at a sufficient level of knowledge. The knowledge possessed by a person does not appear by itself, but is influenced by several factors, including age, environment and social culture.